“When I talk about it, my eyes light up!” Impacts of a national laboratory internship on community college student success - Laleh E. Coté; Seth Van Doren; Astrid N. Zamora; Julio Jaramillo Salcido; Esther W. Law; Gabriel Otero Munoz; Aparna Manocha; Colette L. Flood; Anne M. Baranger (PLoS ONE, 2025)
Participation in technical/research internships may improve undergraduate graduation rates and persistence in science, technology, engineering, and mathematics (STEM), yet little is known about the benefits of these activities a) for community college students, b) when hosted by national laboratories, and c) beyond the first few years after the internship. We applied Social Cognitive Career Theory (SCCT) to investigate alumni perspectives about how CCI at Lawrence Berkeley National Laboratory (LBNL) impacted their academic/career activities. We learned that alumni had low confidence and expectations of success in STEM as community college students. Participation in CCI increased their professional networks, expectations of success, and STEM skills, identity, and self-efficacy/confidence. Hispanic/Latinx alumni recalled the positive impact of mentors who prioritized personal connections, and women valued “warm” social environments. We propose several additions to the SCCT model, to better reflect the supports and barriers to STEM persistence for community college students.